Active earth pressure on translating rigid retaining structures considering soil arching effect. Issue 8 (3rd August 2018) - Zhou, Yi-tao; Chen, Qing-sheng; Chen, Fu-quan; Xue, Xiao-hui; Basack, Sudip
Abstract : Accurate determination of active earth pressure distribution on rigid retaining wall including the magnitude and height of application of its resultant is of immense importance for designing the earth retaining structures. In this paper, an analytical solution based on the soil arching effect is presented. According to Mohr's stress circle, a new relationship between active earth pressure and normal stress on failure surface at any depth from backfill surface is obtained. By analysing parabolic arch of minor principal stresses, a new coefficient of active lateral earth pressure is proposed. The problems that the vertical static equilibrium equation of differential flat element considering soil arching effect is not reasonable are analysed. Then, based on the limit equilibrium of differential flat element, new formulas relevant to the distribution of active earth pressure, the magnitude and height of application of its resultant are derived. The effects of backfill internal friction angle, wall–soil friction angle, wall height, surcharge load and backfill unit weight on those formulas are investigated in detail. In addition, the comparisons of the predictions by proposed equations with available test data as well as existing solutions are carried out, which implies adequate accuracy of the proposed solutions for all ratios of wall–soil friction angle to internal friction angle.